Antenatal Steroids and the IUGR Fetus: Are Exposure and Physiological Effects on the Lung and Cardiovascular System the Same as in Normally Grown Fetuses?. (22nd November 2012) - Morrison, Janna L.; Botting, Kimberley J.; Soo, Poh Seng; McGillick, Erin V.; Hiscock, Jennifer; Zhang, Song; McMillen, I. Caroline; Orgeig, Sandra
Abstract : Glucocorticoids are administered to pregnant women at risk of preterm labour to promote fetal lung surfactant maturation. Intrauterine growth restriction (IUGR) is associated with an increased risk of preterm labour. Hence, IUGR babies may be exposed to antenatal glucocorticoids. The ability of the placenta or blood brain barrier to remove glucocorticoids from the fetal compartment or the brain is compromised in the IUGR fetus, which may have implications for lung, brain, and heart development. There is conflicting evidence on the effect of exogenous glucocorticoids on surfactant protein expression in different animal models of IUGR. Furthermore, the IUGR fetus undergoes significant cardiovascular adaptations, including altered blood pressure regulation, which is in conflict with glucocorticoid-induced alterations in blood pressure and flow. Hence, antenatal glucocorticoid therapy in the IUGR fetus may compromise regulation of cardiovascular development. The role of cortisol in cardiomyocyte development is not clear with conflicting evidence in different species and models of IUGR. Further studies are required to study the effects of antenatal glucocorticoids on lung, brain, and heart development in the IUGR fetus. Of specific interest are the aetiology of IUGR and the resultant degree, duration, and severity of hypoxemia.